The Representation Gap: Change and Reform in the British and American Workplace - Brossard, Michel (Relations industrielles / Industrial Relations, 1999)
The article reviews the book, "The Representation Gap: Change and Reform in the British and American Workplace," by Brian Towers.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z